Echography in liver transplantation: a literature review - L. V. Donova; M. S. Novruzbekov; K. M. Magomedov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Liver transplantation is rightly considered the only radical treatment for terminal chronic liver diseases and patients with acute liver failure. However, despite the accumulated experience in the management of patients in this group, the level of complications development remains at a fairly high level. The success of the correction of emerging pathological conditions largely depends on the timing of their diagnosis. Since complications developing after liver transplantation most often do not have specific clinical and biochemical manifestations, the use of imaging research methods plays a key role in assessing the state of the transplanted organ at all stages of the postoperative period. Among all instrumental methods, ultrasound examination using Doppler techniques, carried out hourly directly in the intensive care unit, with an accuracy of 97 % and a specificity of up to 100 %, makes it possible to detect vascular post-transplant complications as soon as possible. Their timely correction avoids the loss of the graft. The use of dynamic observation contributes to differential diagnosis in identifying non-vascular complications at different stages of the postoperative period. The use of modern techniques greatly expands the possibilities of echography. Thus, the use of contrast enhancement not only shortens the study time, but also increases the sensitivity of Dopplerography in assessing the patency of the vascular bed, especially in patients with decreased central hemodynamics. The use of ARFI-elastography techniques in patients in the late postoperative period makes it possible to objectively assess the severity of hepatic graft fibrosis.